Dropout predictors at gyms: a retrospective study - Gledson Tavares Amorim Oliveira; Lucas Camilo Pereira; Maristela Linhares; Lídia Reniê Fernandes da Silva; Paulo Ricardo Silva; Hassan Mohamed Elsangedy (Colégio Brasileiro de Ciências do Esporte, 2021)
ABSTRACT This study aimed to verify the risk factors associated with gym regulars' dropout over 12 months. This is an observational, retrospective, cohort study. The sample consisted of two gyms (Gym 1: n=2027, age=39.1 ±13.1 years; Gym 2: n=1775, age=36.8 ±11.6 years). Each participant was followed up for 12 months, or until dropout, by controlling the biometric entry system using a turnstile. The adherence rate was of 11% at Gym 1 and 19% at Gym 2. At both gyms, training frequency ≤3x/month and 4-6x/month was associated with dropout. At gym 1, being a female, aged ≥43 years, and enrollment between October and December were dropout predictors. At Gym 2, dropout was associated with contract length ≤31 days and 32-186 days and enrollment between April and December.